Storynomics-Based Branding: Verbal and Visual Strategies for Kompyang Pak Haryono as a Local Culinary Heritage - Damarjati Sinta Maharani (MOZAIK HUMANIORA, 2026)
Developing verbal and visual branding strategies that reflect the cultural value of traditionalfoods is important for preserving local heritage while strengthening market competitiveness.Kompyang, also known askompya, is a traditional bread of Chinese origin adapted to Javanesetastes and now part of Surakarta’s culinary heritage. However,KompyangPak Haryono, the onlyremaining producer in Surakarta, still lacks a formal brand identity, packaging, and presence inmodern commercial spaces. Prior research on traditional culinary branding in Indonesia hasexamined products that already possess a brand identity or has focused on collective regionalbranding, leaving a gap in understanding how a product with no pre-existing brand identity canbe developed into a marketable brand. This study addresses that gap by developing an integratedverbal and visual branding strategy forKompyangPak Haryonothat reflects its cultural values whileincreasing market visibility. Its novelty lies in combining storynomics-based storytelling with vis-ual branding elements to build a brand identity for a heritage product with intergenerationalsignificance. Using a Research and Development (R&D) design with a qualitative approach, datawere collected through observation, interviews, and documentation. The analysis identified theproduct’s branding needs and resulted in a brand name, tagline, logo, packaging design, story-telling narratives, and social media mockups. The study contributes a practical branding proto-type for local producers and creative practitioners, as well as a conceptual contribution to thetraditional culinary branding literature by showing how cultural heritage and contemporarybranding practices can be integrated for a product starting without formal branding history.